Development of an Automated Control System for Brown Sugar Chopping and Drying Machine Based on Outseal PLC Nano V.5 - Hakim, Aulia el; Yudha, R. Gaguk Pratama; Saputra, Angga Dwi; Mahmud, Ahmad Ulil Albab (Journal of Telematics and Informatics, 2025)
This study presents the development of an automated control system for a brown sugar chopping and drying machine using Outseal PLC Nano V.5. The system significantly enhances chopping efficiency, reducing processing time by 45% compared to conventional methods. The drying process is optimized using automated temperature control with a PT100 sensor, ensuring a consistent moisture reduction of 80% in the final product. Regression analysis results show a strong correlation (R² = 0.92) between drying time and moisture reduction, confirming the system's effectiveness. The integrated automation successfully maintains a stable drying temperature, preventing overheating and preserving product quality. These advancements contribute to increased productivity, improved product consistency, and a more efficient brown sugar processing system. Future research can explore further refinements in airflow management to enhance drying uniformity. This system modernizes traditional brown sugar processing and supports automation for higher efficiency and sustainability.